The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.organomet.5b00396
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structures of [CH2(NCnH2n)2]Mo(CO)4 (n = 4,5) Complexes with Bis(cycloamine) Ligands Easily Prepared from CH2Cl2

Abstract: Dipyrrolidylmethane, CH 2 (pyr) 2 , and dipiperidylmethane, CH 2 (pip) 2 , are synthesized via the condensation of their respective secondary amine precursors and dichloromethane at room temperature in the absence of light. Their use as chelating ligands is shown by the isolation and complete characterization of [CH 2 (pyr) 2 ]Mo(CO) 4 and [CH 2 (pip) 2 ]-Mo(CO) 4 complexes. X-ray analysis reveals the methylene bis(cycloamines) to possess a sharp bite angle between 61°and 63°and a strong steric impact on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Similar types of reactions were reported with pyridine, pyrrole, carboxylic acids or aldehydes using DCM as methylene source for the construction of bis‐type molecules. Recently, Liu et al .…”
Section: Reaction Solvents As Precursors For the Installation Of Key supporting
confidence: 56%
“…Similar types of reactions were reported with pyridine, pyrrole, carboxylic acids or aldehydes using DCM as methylene source for the construction of bis‐type molecules. Recently, Liu et al .…”
Section: Reaction Solvents As Precursors For the Installation Of Key supporting
confidence: 56%
“…54,57 Even during the chelation of cyclic diamines to metal carbonyls, the two N atoms displace the CO from cis positions, which only results in a slight distortion in the overall octahedral geometry. 58 To support this idea that OLA forms an intermediate or new complex with W(CO) 6 with a local, octahedral symmetry, we also looked into the coordination reactions of OLA with W(CO) 6 by DFT (Section S10 in the Supporting Information). The high reaction temperature and inert atmosphere of the reaction flask help drive the endothermic formation of W(CO) 6−x (OLA) x species, which remains quasi-octahedral.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“… 43 Dipyrrolidylmethane CH 2 (pyr) 2 and dipiperidylmethane, CH 2 (pip) 2 were synthesized via the condensation of the secondary amine precursors and DCM at room temperature in the absence of light. 44 Another reaction of amines with methylene chloride yielded aminals rapidly. 45 Matsumoto et al reported the reaction of DCM with ketones or esters in the presence of secondary amines at high pressure whereby DCM was used as methylene bridge in forming both C–C and C–N bonds.…”
mentioning
confidence: 99%